Pokca (Pojok Membaca) Gerakan Peningkatan Literasi Membaca di SDN Tisnogambar 02 Desa Tisnogambar - Iswahyudi, Iswahyudi; Fais, Ahmad Nur; Haq, Raka Ainul; Priyananda, Dhiaz Ari (P3M Politeknik Negeri Jember, 2024)
Reading literacy is still a serious problem in Indonesia, the results of PISA (Program fot Internaiional Student Assesment) in 2022 show that Indonesia is still ranked 11th in the bottom of the 81 countries recorded, this will have an impact on the low knowledge of students in Indonesia. SDN Tisnogambar 02 is also still a school that does not like reading, according to a survey conducted by the Real Work Lecture (KKN) 03 group. Therefore, Pokja (Reading Corner) activities can be a forum for students to improve reading literacy in Indonesia, especially for SDN Tisnogambar 02, which is carried out by the Real Work Lecture (KKN) 03 group. Implementation of Pokca (Reading Corner) activities starts from the planning, preparation, implementation and evaluation stages, where incentives are carried out for one month. With this Pokca (Reading Corner) activity, the habit of reading at SDN Tisnogambar 02 students begins to develop, this leads to setundents’ interest in reading creasing.